2019
DOI: 10.3390/ijms20246108
|View full text |Cite
|
Sign up to set email alerts
|

Proteome and Ubiquitome Changes during Rose Petal Senescence

Abstract: Petal senescence involves numerous programmed changes in biological and biochemical processes. Ubiquitination plays a critical role in protein degradation, a hallmark of organ senescence. Therefore, we investigated changes in the proteome and ubiquitome of senescing rose (Rosa hybrida) petals to better understand their involvement in petal senescence. Of 3859 proteins quantified in senescing petals, 1198 were upregulated, and 726 were downregulated during senescence. We identified 2208 ubiquitinated sites, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 81 publications
(121 reference statements)
1
10
0
Order By: Relevance
“…Proteolysis is recognized as key step during onset of flower senescence as reported in Rosa (Lu et al, 2019). Treatment with polyamines maintained higher concentration of soluble proteins in the tepal tissues as compared to untreated ones.…”
Section: Discussionmentioning
confidence: 77%
“…Proteolysis is recognized as key step during onset of flower senescence as reported in Rosa (Lu et al, 2019). Treatment with polyamines maintained higher concentration of soluble proteins in the tepal tissues as compared to untreated ones.…”
Section: Discussionmentioning
confidence: 77%
“…However, no relative research about ubiquitome has been conducted in LECs. With the rapid development of omics technologies, a growing number of studies are prone to use this high-throughput method to analyze the molecular mechanisms of different diseases. ,, In this study, we simultaneously conducted proteome and ubiquitome sequencing for the first time to explore the changes in the quality and quantity of proteins in UVB-induced oxidative damage model and offer novel insights into the molecular mechanisms of ARC.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 7,026 K ub sites, 5,025 unique sites were assigned to 13 conserved motifs (Supplementary Figure 3A), which accounted for approximately 71.5% of the sites identified. Nine of these 13 motifs have been reported previously (Xie et al, 2015;Guo et al, 2017;Lu et al, 2019;Fan et al, 2021), while the other 4 motifs are novel: K ub Q, DNK ub , DNNK ub , and ENNNNNNK ub (where N indicates any amino acid). In addition, we observed that 4 distinct residues were enriched around K ub , including alanine (A), glutamate (E), aspartate (D), and glutamine (Q).…”
Section: Ubiquitination Changes In Az During Petal Abscissionmentioning
confidence: 98%
“…Automatic gain control was set at 5E4. MS/MS data processing and bioinformatic analysis were performed as previously described (Lu et al, 2019).…”
Section: Lc-ms/ms Analysismentioning
confidence: 99%
See 1 more Smart Citation